2007
DOI: 10.1186/1477-7819-5-51
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in colorectal neoplasms: is there an aetiological relationship?

Abstract: Background: This pilot study was carried out to determine whether Helicobacter pylori can be detected in normal colon or in association with colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 45 publications
6
66
1
1
Order By: Relevance
“…The prevalence of H. pylori was higher in villous type polyps than in tubular type polyps and adenocarcinomas. Contrary to this finding, Jones et al (2007) demonstrated that villous adenoma had the lowest rate of H. pylori positivity compared to other premalignant and malignant colonic lesions. Their results also showed significant associations of H. pylori positivity with tubular and tubulovillous adenomas, and adenocarcinomas, but not with villous adenomas.…”
contrasting
confidence: 51%
“…The prevalence of H. pylori was higher in villous type polyps than in tubular type polyps and adenocarcinomas. Contrary to this finding, Jones et al (2007) demonstrated that villous adenoma had the lowest rate of H. pylori positivity compared to other premalignant and malignant colonic lesions. Their results also showed significant associations of H. pylori positivity with tubular and tubulovillous adenomas, and adenocarcinomas, but not with villous adenomas.…”
contrasting
confidence: 51%
“…Some studies were able to identify the genetic material of the bacteria in colonic neoplasias (3,8,15) . The effect of the intestinal flora as a carcinogenic agent has been evaluated and the possibility exists that bacteria such as H. pylori circulating in the intestines could directly activate carcinogenesis (33) .…”
Section: Resultsmentioning
confidence: 99%
“…Like serologic studies, studies using PCR methods have been equivocal. Two studies found that detection of H. pylori via PCR was significantly higher in colorectal adenocarcinoma tissues compared with normal colorectal tissues (Grahn et al, 2005;Jones et al, 2007), but a third study found that only 1.2% of malignant colorectal tissue samples were positive for H. pylori, compared with 6% of normal tissues (Bulajic et al, 2007). The 13C-urea breath test has 97% sensitivity and specificity in H. pylori detection (Chen et al, 2003); however, as in PCR-based studies, the evidence is not convincing.…”
Section: Discussionmentioning
confidence: 98%